All-optical logic NOT gate for Manchester encoded signal using a reflective semiconductor optical amplifier - Hu, Zhefeng; Sun, Junqiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We propose and experimentally demonstrate an all-optical Manchester NOT gate. A logic NOT signal is realized for a 10 Gb/s Manchester encoded signal, based on cross-gain modulation (XGM) in a reflective semiconductor optical amplifier (RSOA).
Optica Applicata, Vol. 40, 2010, nr 1, s. 57-61
Keywords: optyka; all-optical logic; cross-gain modulation (XGM); reflective semiconductor optical amplifier (RSOA); Manchester code